Discovery of Marine Macrozoobenthos Fossils in the River of Wonocolo Geosite, Indonesia - Rahmawati, Laily Agustina; Afiati, Norma; Putranto, Thomas Triadi (Faculty of Geography, Universitas Gadjah Mada, 2024)
Wonocolo Geosite is a geoheritage known for the existence of the Kawengan Anticlinal Trap, which is the only one in the world, causing oil to be found in shallow locations. This condition has allowed for traditional mining since the Dutch colonial era and continues today. Geological history states that the anticlinal structure was formed when the Indo-Australian plate collided with the Eurasian plate, resulting in folds and uplift of the seafloor above the surface. However, there has not been much research supporting the truth of the theory. Therefore, evidence is needed to support the uniqueness of the Wonocolo Geosite. The fossil collection method was carried out simultaneously with the collection of substrates at the upstream, middle, and downstream riverbeds using 20 cm diameter PVC pipes at a depth of 10 cm.This study found marine macrozoobenthos fossils during substrate sampling in the upstream, middle, and downstream river beds using a PVC pipe with a diameter of 20 cm at a depth of 10 cm. The samples were then identified in the laboratory, revealing fossils from the deep sea. The fossils found include Azooxanthellate (Cnidaria), which lives at depths of up to 2000 m; Dentaliida (Mollusca) which lives at depths of 500-7000 m and Foraminifera which also live in the deep sea. This phenomenon is unusual, considering that the fossils were found in a river far from the sea at an altitude of 250 MASL. Therefore, the discovery of marine macrozoobenthos fossils at the bottom of the Wonocolo River strengthens the theory of the formation of the Wonocolo Formation from a raised seabed which is also an important asset supporting the Wonocolo Geoheritage.